Fentanyl dose for the insertion of classic (TM) laryngeal mask airways in non-paralysed patients induced with propofol 2.5 mg/kg - Tan, A.S.B.; Wang, C.Y. (Australian Society of Anaesthetists, 2010)
The aim of this randomised, controlled trial was to determine the optimum dose of fentanyl in combination with propofol 2.5 mg.kg(-1) when inserting the Classic (TM) Laryngeal Mask Airway. Seventy-five ASA I or II patients were randomly assigned to five groups of fentanyl dosage: 0 mu g.kg(-1) (placebo), 0.5 mu g.kg(-1), 1.0 mu g.kg(-1), 1.5 mu g.kg(-1) and 2.0 mu g.kg(-1). Anaesthesia was induced by first injecting the study drug over 10 seconds. Three minutes after the study drug was injected, propofol (2.5 mg.kg(-1)) was injected over 10 seconds. The Classic (TM) Laryngeal Mask Airway was inserted four minutes and 30 seconds after injection of the study drug. Insertion conditions were evaluated using a four-category score. Thirty-nine males and 36 females aged 19 to 59 years were studied. The incidence of prolonged apnoea increased as fentanyl dose increased. We found that there was a high rate of successful first attempt at insertion with 1 mu g.kg(-1) and 1.5 mu g.kg(-1), 93% and 87% respectively; compared to 87% in the 2.0 mu g.kg(-1) group. The 1.0 mu g.kg(-1) group also achieved an 80% optimal insertion conditions score of 4, compared to 73% in the 1.5 mu g.kg(-1) group and 80% in the 2 mu g.kg(-1) group. Therefore we recommend 1.0 mu g.kg(-1) as the optimal dose of fentanyl when used in addition to propofol 2.5 mg/kg for the insertion of the Classic (TM) Latyngeal Mask Airway.